Students’ Perception of Code Mixing and Code Switching Used by The Teacher at SMA Negeri 5 Samarinda - Rohman , Abdul; Badriyah , Fadlilatul; Bali Geroda, Godefridus (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2024)
The one of language switching effects is the use of code switching and code mixing in the classroom. English become one of compulsory subjects at all of school in Indonesia, so the teacher and students sometimes speak Indonesian during learning process. The use of code switching and code mixing in the classroom often used by teacher in Indonesia. This research was conducted at eleventh grade social-4 in SMA Negeri 5 Samarinda. Data collection in this research the researcher used qualitative research and for selection the students are using snowball sampling, and that is including in non-probability sampling. The results of this research are student perception was had a good perception about teacher used code mixing and code switching in learning process. Liked S1 said “Yes I agree if used during teaching learning process” another S3 said I Strongly agree because can help me to understanding English. Most of students agree with that because made them easier for study to understanding the material what teacher explained.